THE ROLE OF BRAIN PLASTICITY IN THE FUNCTIONAL ADAPTATION OF BODY AT CEREBRAL INFANTILE PARALYSIS WITH THE AFFECTION OF HANDS - A. A. Baranov; O. A. Klochkova; A. L. Kurenkov; L. S. Namazova-Baranova; S. S. Nikitin; A. R. Artemenko; A. M. Mamedyarov (Педиатрическая фармакология)
Cerebral infantile paralysis (CIP) is the main neurologic reason of children's disability all over the world. A competent choice of time and methods of rehabilitation allows social adaptation of children with this pathology and improves their motor and mental development prognosis. The article gives modern data on the neuronal plasticity, spare capacities of the developing brain, pathophysiological aspects of restoration and compensation of damaged structures of central nervous system. The emphasis is put on the consideration of neuroplasticity mechanisms from the point of view of their clinical relevance and role in the formation of pathological and compensatory patterns of movement and perception at CIP. Variants of restoration of motor and sensory functions in upper extremities of children with CIP based on the time and topics of brain damage are analyzed in detail. Approaches to pathogenetically grounded choice of methods and time of rehabilitation are discussed on the basis of the given data on spare capabilities of children's nervous system with the emphasis on restoration of upper extremities' function as one of the most complicated, although prospective, aspects of CIP treatment.